2020
DOI: 10.1002/hbm.24879
|View full text |Cite
|
Sign up to set email alerts
|

Nonreplication of functional connectivity differences in autism spectrum disorder across multiple sites and denoising strategies

Abstract: A rapidly growing number of studies on autism spectrum disorder (ASD) have used resting‐state fMRI to identify alterations of functional connectivity, with the hope of identifying clinical biomarkers or underlying neural mechanisms. However, results have been largely inconsistent across studies, and there remains a pressing need to determine the primary factors influencing replicability. Here, we used resting‐state fMRI data from the Autism Brain Imaging Data Exchange to investigate two potential factors: deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 70 publications
(154 reference statements)
5
49
0
Order By: Relevance
“…Whether a brain network marker constructed in the first stage generalizes to the data acquired from multiple completely different imaging sites is a crucial issue for the above hierarchical supervised/unsupervised approach [20][21][22]. However, an increasing number of studies have highlighted the difficulty in generalization of the brain network marker to the data acquired from multiple completely independent imaging sites, even using the supervised learning method [14,23]. For example, in a recent paper by Drysdale, which is one of the most…”
Section: Introductionmentioning
confidence: 99%
“…Whether a brain network marker constructed in the first stage generalizes to the data acquired from multiple completely different imaging sites is a crucial issue for the above hierarchical supervised/unsupervised approach [20][21][22]. However, an increasing number of studies have highlighted the difficulty in generalization of the brain network marker to the data acquired from multiple completely independent imaging sites, even using the supervised learning method [14,23]. For example, in a recent paper by Drysdale, which is one of the most…”
Section: Introductionmentioning
confidence: 99%
“…The absence of reliable and specific cross-etiological molecular or genetic biomarkers for ASD 1,39 have prompted research into the use of functional neuroimaging readouts as possible point of convergence for a diagnostic or prognostic characterization of ASD. However, until now connectivity studies in ASD patients have revealed highly heterogeneous and inconsistent results, which has fueled discussion regarding the clinical utility of imaging markers in ASD 40 . Here, we capitalized on recent advances in rodent rsfMRI 19,20,4144 to measure connectivity across 16 different ASD mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our study is based on a large cohort of patients with ASD (N = 880), obtained from the ABIDE initiative, and it combines anatomical and functional neuroimaging data from 24 different institutions. Second, we have used Combat to conduct functional connectivity studies, a highly rigorous method to eliminate the variability between MRI scans across the 24 institutions, one of the largest sources of variability when combining data from multiple institutions (71). Third, our analysis of brain connectivity was carried out on a large-scale, where each brain region is…”
Section: Discussionmentioning
confidence: 99%